Analysis of the demand for life insurance and family Takaful: The ARDL modeling / Hendon Redzuan - Redzuan, Hendon (2011)
The main objective of this study is to identify the determinants of life insurance and family takaful demand in the Malaysian marketplace. An interest in understanding the driving factors behind the purchase of life insurance has been growing since the first empirical study on the subject was conducted by Hammond et al. (1967). Even after 50 years, the quest to discover the determinants of life insurance demand continues with many recent empirical studies exploring these factors in a specific market or crosscountry context. This study seeks to broaden the existing literature relating to the demand for life insurance by investigating the key determinants of the consumption of life insurance specific to the Malaysian economy. The life insurance market in Malaysia is grossly under-tapped and what drives the demand for life insurance in Malaysia is still not well understood. This study applies the ARDL approach to cointegration advanced by Pesaran, Shin and Smith (2001), to examine the relationship between life insurance demand and a set of theoretically identified variables. The ARDL approach estimates the long-run coefficients and the associated error correction model after establishing the cointegration relationship among the variables under study. Using annual time series data for the period 1970 through 2008, eight versions of the demand model were developed and estimated to provide evidence on the long- and short-run relationships between life insurance and family takaful demand in Malaysia. The empirical results suggest that income is the key determinant in the consumption of life insurance both in the long- and short-run. Evidence also suggests that income has a significant influence on family takaful consumption in the long-run, but its effect is less obvious in the short-run. The number of dependents, level of education, savings in the Employees' Provident Fund (EPF), life expectancy and price of insurance are among the other factors that have a significant impact on the demand for life insurance and family takaful. The results also show the beneficial role of financial development in stimulating the growth of insurance sector. The main contribution of this thesis lies in its ability to empirically identify the determinants of both life insurance and family takaful demand and their short- and longrun relationships using the recent ARDL approach. The findings will provide important information for the insurers and policy makers to formulate new policies and strategies to further develop and promote the insurance industry.